Krieg im Krieg
This broadcast focuses on the infighting between rival Muslim and Croat factions in and around Mostar. Muslim civilians are interviewed in Eastern Mostar as well as soldiers from both sides, a spokesman for the Croatian HVO, and Muslim prisoners speaking about forced labor and beatings. Footage of civilian destruction is shown throughout the report. The conditions found in smaller towns such as Prozor, Vitez, Kiseljak, Vares, and Gornji Vakuf are highlighted. Interviews with Muslim and Croat city officials and military personnel. The UN presence and the role of NATO in the region are briefly touched upon.